Detection of dibutyl phthalate in food samples by fluorescence ratio immunosensor based on dual-emission carbon quantum dot labelled aptamers. Issue 1 (1st January 2020) - Wang, Ximo; Chen, Chen; Chen, Yongfeng; Kong, Feifan; Xu, Zhixiang
ABSTRACT: This study reports a fluorescence ratio immunosensor method for detecting dibutyl phthalate (DBP) sensitively and specifically using dual-emission carbon quantum dots labelled with amino-modified nucleic acid aptamers. Under optimal experimental conditions, the linearity range of the method for detecting DBP was from 12.5 to 1500 μg/L, with a limit of detection of 5.0 μg/L. Compared with detection results for two structural analogues, this method showed good specificity for DBP. Liquor samples spiked with DBP measured by this method exhibited a standard recovery of 93.2% to 112.4% with a relative standard deviation of 1.59% to 4.54%. The method was used to determine the DBP content in edible oil samples, providing results not significantly different from those obtained by gas chromatography. Compared with the single wavelength emission method, this method had a stronger anti-interference ability and provided more accurate results, so can be used for highly sensitive detection of DBP in food samples.